(Invited) Which LIB Cathode Will Dominate for the EVs and ESS --- from the Industry Point of View?. (25th October 2017) - Xu, Zhiyong; Han, S; Tao, L.-Q.; He, L.-Y.; Yi, Z.-L.; Huang, Y.-F.; Ye, L; Gu, T
Abstract : Lithium ion batteries (LIBs) have been widely and profoundly changing people's ways of life. For the LIBs, there has always been an argument that which cathode will dominate in their various applications, especially for electric vehicles (EVs) and energy storage systems (ESS). In this talk, we outline pros and cons for each cathode material from the industry point of view. The criteria to judge advantages and disadvantages include cost, safety, cycle life, rate capability, recycling capability, energy density, mass production capability, toxicity, and working temperature range etc. We also present an approach to get a better lithium iron phosphate cathode material.